Jorid's big book of Christmas knits : over 70 Scandinavian holiday patterns - Linvik, Jorid (Trafalgar Square Books, 2019)
Jorid Linvik, bestselling author of Big Book of Knitted Mittens and Big Book of Knitted Socks, is back with an all-new collection of patterns: over 70 projects bursting with holiday cheer! Including gifts and accessories of all sizes, from garments to home décor, plus toys, Christmas ornaments, and so much more--enough to keep knitters of all skill levels busy all year round. Whether you're a planner who preps for Christmas months in advance, or you're looking for a fast, fun gift at the last minute, the perfect pattern is waiting for you, with Jorid's trademark flair, color, and sense of style.